Dějiny napsané na zeď. K Benjaminovu pojmu aktuality - Marek Kettner (Reflexe, 2023)
The study aims to explain the meaning and function of the concept of topicality (Aktualität) in Benjamin’s philosophy of history and to show that it can present a relevant alternative to contemporary historiography. In times when society is improving the accuracy of its grasp of history and accumulating ever more data about it, Benjamin’s philosophy is valuable by concerning itself primarily with the problem of presentation (Darstellung) of the topicality of particular historical phenomena. Thanks to a better understanding of the concept of topicality, the reader will be able to see why Benjamin thought that to respond to what is “actual” in the sense of “topical” or “timely” in history is more important than specifying or accumulating data about it. However, in the presentation of a single topical historical object the whole of history is monadologically expressed: Benjamin’s focus on particular, unique phenomena didn’t imply a resignation vis-à-vis the task of expression of the whole.